Capitu Between Two Enigmas: Veridiction and Fiduciary Contract - Mendes, Mariza Bianconcini Teixeira (Estudos Semióticos, 2011)
This work intends to present a new approach to Dom Casmurro, the most enigmatic novel by Machado de Assis, in order to study the features of veridiction and the ﬁduciary contract in the epistemic relation involving the enunciator and enunciatee of discourse, and the discourse actors, Bentinho/Bento and Capitu/Capitolina. These relations are intermediated in this literary discourse by the subjective point of view of the narrator Dom Casmurro, who is willing to remember, in a new context of time and space, the actions and reactions of his emotional life. His aim was to unveil and understand the chief mysteries involving his terrible passionate impulses. This enunciation procedure makes the novel a special object for a semiotic analysis of the ﬁduciary contract. Greimas, creator of French semiotics (1983, 1987), Fontanille (1999) and Bertrand (2003) form the theoretical basis of this analysis, which searches for the intersection between veridiction, ﬁduciary contract, point of view, rhetoric and ﬁgurativity of passions in literary discourse. Two literary ﬁgures – “dissimulated and oblique gypsy eyes” and “rip tide eyes” (“olhos de ressaca”) – were chosen as isotopic connectors, responsible for the semantic chain and the rhetoric dimension of discourse. The hypothesis to be conﬁrmed is that those ﬁgures give support to the meanings of the ﬁduciary relations analysed in the literary discourse.